The Russian Default and the Contagion to Brazil - Baig, Taimur (IMF Working Papers; Working Paper ;, 2000)
This paper investigates the contagion from Russia to Brazil in late 1998 under two dimensions- players involved and the timing of events. The data does not seem to reflect a compensatory liquidation of assets story by international institutional investors. It does contribute, however, to the suspicion that the contagion was triggered by foreign investors panicking from the Russian crisis, and joining local residents on their speculation against the Brazilian real. Adjusted correlations in the Brady market increase significantly during the crisis, which lends support to the view that if there was a contagion from Russia to Brazil, the most likely place of the transmission was the off-shore Brady market. Finally, the paper does not support the hypothesis that it was the liquidity crisis in mature markets, and not the Russian crisis, that timed the crisis in Brazil.